Security, the state, and the citizen: the changing architecture of crime control - Zedner, L (University of California Press, 2010)
Citizenship has become a buzz word of political discourse and policy formation. Recent formulations convey the message that rights are contingent on earning membership in a political community and carry corresponding responsibilities. Acquiring citizenship entails a more rigorous process of validation and conformity with prescribed norms. The notion of probationary citizenship (developed in respect of immigrants) is extended to all those whose standing as full citizens is in doubt. Citizenship comes to be used as a means of policing and a tool of the criminal law. Assertion of the states' duty to provide security for bona fide citizens provides the rationale for measures that are preemptive, exclusionary, and pay scant regard to precedural proprieties. They create a caste of outlaws and aliens whose status renders them suspect aside from any wrongdoing; whose interests are compromised in the name of protecting the public; and who must requalify to enjoy full citizenship. One means of resisting these trends is adherence to a liberal model of the criminal law and assertion of due process protections as security rights for all individuals against the state.